Exploring the mechanism of the Fructus Mume and Rhizoma Coptidis herb pair intervention in Ulcerative Colitis from the perspective of inflammation and immunity based on systemic pharmacology - Yatian Yang; Chengcheng Qian; Rui Wu; Rui Wang; Jinmei Ou; Shoujin Liu (BMC, 2023)
Abstract Purpose Ulcerative Colitis (UC) is a chronic nonspecific inflammatory disease of the colon and rectum. Fructus Mume (FM) and Rhizoma Coptidis (RC) exert effects on inflammatory and immune diseases. We evaluated the hypothesis of the FM and RC (FM-RC) herb pair remedy in alleviating dextran sulfate sodium (DSS)-induced colitis, through network pharmacology-based analyses, molecular docking, and experimental validation. Methods The Traditional Chinese medicine systematic pharmacology analysis platform(TCMSP) and Swiss database were used to predict potential targets of FM-RC and the GeneCards database was utilized to collect UC genes. Cytoscape software was used to construct and analyze the networks, and DAVID was utilized to perform enrichment analysis. AutoDock software was used to dock the core chemical components of the FM-RC herb pair with key UC targets. Animal experiments were performed to validate the prediction results and general conditions and body weight were observed. Pathological changes in colon tissue were observed by staining with hematoxylin and eosin. The levels of TNF-α, IL-8, IL-17, and IL-4 in serum and colon tissue were detected by ELISA. Results Eighteen effective components of the herb couple were screened, and their potential therapeutic targets in the treatment of UC were acquired from 110 overlapped targets. GO and KEGG analyses revealed that these targets were highly correlated with protein autophosphorylation, plasma membrane, ATP binding, cancer pathways, the PI3K-AKt signaling pathway, and the Rap1 signaling pathway. Molecular docking established the core protein interactions with compounds having a docking energy < 0 kJ·mol−1, indicating the core active components had strong binding activities with the core targets. FM-RC herb pair relieved pathological indicators and reduced the concentration of TNF-α, IL-8, and IL-17 and increased IL-4 levels in the serum and colon tissues of UC rats. Conclusion Collectively, FM-RC herb pair administration alleviated UC. These beneficial effects targeted MAPK1 signaling related to inflammation and immunity, which provided a basis for a better understanding of FM-RC in the treatment of UC.